Criminal Offence of Forest Theft in Current Legislation of the Republic of Serbia - Batrićević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
Although there is no doubt about the ecological, medical, social and economic importance of forests on both the global and national level, information on their rapid disappearance and degradation causes reasonable concern among experts from various scientific fields, including criminal law, as the "ultima ratio" for the oppression of harmful, socially hazardous and unacceptable activities. Accordingly, the current Criminal Code of the Republic of Serbia incriminates forest theft as one of the criminal offences against the environment. In this paper, the author analyses the definition, elements, characteristics and forms of this criminal offence, criminal sanctions that can be imposed on its perpetrator and certain dilemmas that such cases might cause in judicial practice. Moreover, based on available statistical data on ecological crimes in the Republic of Serbia for the period between 2006 and 2011, the author attempts to depict the range and the dynamics of forest theft and its share in the overall ecological crime in our country. Finally, the author points out some weaknesses of the present social reaction to this form of crime and offers constructive suggestions for its improvement in accordance with international standards.